a) 2011 . 2013 = 2011 . ( 2012 + 1 ) = 2011 . 2012 + 2011
20122 = 2012 . 2012 = ( 2011 + 1 ) . 2012 = 2011 . 2012 + 2012
Vì 2011 . 2012 + 2011 < 2011 . 2012 + 2012 nên 2011 . 2013 < 20122
(3+4)2=32+42
Vì 32+42=32+42 nên (3+4)2=32+42
2300=(23)100=8100
3200=(32)100=9100
Vì 8100<9100 nên 2300<3200
\(\left(3+4\right)^2=3^2+4^2\)
Vì \(3^2+4^2=3^2+4^2\)nên \(\left(3+4\right)^2=3^2+4^2\)
\(2^{300}=\left(2^3\right)^{100}=8^{100}\)
\(3^{200}=\left(3^2\right)^{100}=9^{100}\)
Vì 9>8 nên \(2^{300}< 3^{200}\)
Ta co
2012^2=2012.2012
=2012.(2011+1)
=2012.2011+2012
2011.2013=2011.(2012+1)
=2011.2012+2011
Vi 2011.2012+2011<2012.2011+2012(vi 2012>2011) nen 2012^2>2011.2013
(3+4)^2 va 3^2 +4^2
=> 7^2 va 9+16
=> 49 va 25
vi 49>25 nen (3+4)^2 > 3^2+4^2
3^200 va 2^300
Ta co
3^200=(3^2)^100=9^100
2^300=(2^3)^100=8^100
Vi 8^100<9^100 => 3^200>2^300
c,2 mũ 300 < 3 mũ 200 vì
2 mũ 3 =8 ; 3 mũ 2=9
Nên 2 mũ 300 < 3 mũ 200